2011
DOI: 10.1007/s00705-011-1157-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a new begomovirus that infects Euphorbia heterophylla and Solanum lycopersicum in Venezuela

Abstract: We report the complete nucleotide sequence of a begomovirus isolate infecting Euphorbia heterophylla and tomato (Solanum lycopersicum) in central Venezuela. Based on the current taxonomic criteria for the genus Begomovirus, the isolate was shown to represent a novel species, tentatively named Euphorbia mosaic Venezuela virus (EuMVV). Its DNA-A is most closely related to those of Euphorbia-infecting begomoviruses from the Caribbean and Central America. The DNA B component forms a phylogenetic cluster with Eupho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…EuMVV, TYMLCV and ToCLDV have been described recently (Zambrano et al. , ; Nava et al. ); however, there are no data concerning their host ranges and vector transmission efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EuMVV, TYMLCV and ToCLDV have been described recently (Zambrano et al. , ; Nava et al. ); however, there are no data concerning their host ranges and vector transmission efficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…So far, six begomovirus species have been described infecting tomato in Venezuela: the New World (NW) begomoviruses PYMV, Euphorbia mosaic Venezuela virus (EuMVV), Merremia mosaic virus (MeMV), Tomato chlorotic leaf distortion virus (ToCLDV), Tomato yellow margin leaf curl virus (TYMLCV) and the Old World (OW) begomovirus Tomato yellow leaf curl virus (TYLCV) (Zambrano et al. , , ; Nava et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotiana benthamiana is a laboratory host used as a model plant for many plant virus studies. Therefore, systemic replication of MeCMA in this host provides opportunities for further studies involving other begomoviruses whose presence has also been reported in the same growing areas infecting cultivated and non‐cultivated plants (Zambrano et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, disease outbreaks in melon crops from Colombia have been associated with a begomovirus that has been partially sequenced and seems to be a member of the SLCV clade (Morales & Anderson, 2001). Excluding MeCMV, the South American members of the SLCV clade have been isolated from Euphorbia spp., mainly Euphorbia heterophylla (Paprotka et al, 2010;Fernandes et al, 2011;Zambrano et al, 2012) which are common weeds that grow around crops (Zambrano et al, 2012). After introduction of the B biotype of B. tabaci in Latin America, local begomoviruses that were poorly transmitted by indigenous B. tabaci biotypes emerged, developing severe outbreaks due to the high transmission efficiency of the B biotype (Morales & Anderson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The CR is informative about genetic diversity because it is the most variable part of begomoviruses genome (Padidam et al 1995;S anchez-Campos et al 2002). This analysis has been used for study the diversity of begomoviruses in distinct hosts from several countries on different collecting dates (Faria and Maxwell 1999;Ribeiro et al 2003;Fernandes et al 2008;Trisno et al 2009;Zambrano et al 2012;Quiñones-Pantoja et al 2014). Positive samples showed the presence of DNA-A and DNA-B indicative of bipartite begomoviruses, and it was not possible to precisely identify each virus.…”
Section: Discussionmentioning
confidence: 99%